(untitled) (International Journal of Studies in Nursing, 2019)
Background: Female Genital Cutting is a complex issue requiring continuing care for girls and women who may be at risk or may have been undergone this harmful practice. Objective: Assess the experiences of Female Genital Cutting and its relation to sexual satisfaction among rural women in El Beheria Governorate. Design: cross-sectional descriptive design. Settings: The study was carried out at 16 rural health units representing the 16 health zones in El Beheria Governorate. Subjects: A convenience sample of 800 women selected from the previously mentioned setting (50 from each health unit). Tools: Two tools were used for data collection. The first tool was women’s experience of FGC structured interview schedule to identify data related to personal and socio-demographic characteristics, their experience of FGC, as well as their attitude towards FGC, which was assessed through 21 statements in three points Likert scale. The second tool was sexual satisfaction Scale to assess the sexual satisfaction among the married women. Results: Findings of the present study revealed that the majority (90.0%) of the women had undergone FGC. Moreover, less than two thirds (63.0%) of the women had positive attitude toward combating FGC. Additionally, around one tenth 9.8% of the women suffered from low sexual satisfaction compared to 18.4% of them who had high satisfaction. Moreover, significant correlations were found between women’s experience of FGC and their attitude toward it as well as with their sexual satisfaction. Conclusion: The study concluded that FGC is highly prevalent practices among rural women. There are a significant association between women’s experience of FCG and their attitude towards it as well as with the women’s sexual satisfaction.